Future crop suitability assessment and the integration of Orphan crops into Kenya's food systems - Joshi, Namita (Department of Environmental and Geographical Science, 2022)
Climate change is seen to be playing an increasingly key role in determining the level of food security within Kenya. In 2020, around 3.1 million people in the country faced acute food insecurity as a result of excessive rainfall, flooding and drought. There has also been a concentration of research on major crops, such as maize and common bean. This study, therefore, seeks to contribute to the research gap in future projections of crop suitability for major and minor crops in Kenya. Temperature and rainfall data, downloaded from CORDEX, from four statistically downscaled Global Climate Models (GCMs) under the Representative Concentration Pathways (RCP) 8.5 and 4.5 were used to run the Ecocrop model. The output was the suitability index spatially plotted over the country for maize, finger millet, common bean, broad bean and sweet potato, within three time periods: historical (1980-2009), near term (2010- 2039) and midcentury (2040-2060). To further understand the influence soil pH has on the climate suitability of these five crops, QGIS was used to overlap Ecocrop suitability outputs and Soilgrids soil pH rasters. CORDEX projections indicated a 2°C- 2.5°C and 1°C rise in temperature under RCP8.5 and 4.5 respectively, and rainy seasons becoming more intense and shorter. The suitability index of maize is projected to have a slight increase (20%) during the long rains, by the end of the century under RCP8.5. Along the RCP4.5 pathways, there is a greater increase in suitability for maize in counties along the coast and western Kenya. Results also project a significant suitability increase (50%) of the orphan crop- broad bean- during the dry season. The spatial distribution of suitability is widespread within many arid and semi-arid counties. This presents an opportunity to integrate legumes such as broad bean into the cropping system within a crop rotation with maize. This form of adaptation would help ease the pressure on the production of staple crops since suitability for maize and common bean is projected to decrease during the short rains. Soil pH results indicated the dominance climate has on determining overall suitability. For instance, pH suitability of finger millet was achieved in majority of the counties however, climate suitability does not favour the planting of this crop. For sweet potato, there is optimum pH and climate suitability, however, it is not greatly distributed around the country. Despite the low spatial distribution, these small areas of sweet potato production can also contribute to better food security in these counties.